From Slavery to Sovereignty: The Transformation of Arung Palakka's Masculinity in Bugis History - Ilham (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2025)
The transformation of Arung Palakka's masculinity from a nobleman to a leader is a complex narrative shaped by his extreme experiences as an enslaved person. This research, which uses a historical-qualitative approach, analyzes how collective trauma and Bugis cultural values such as siri (honor/self-esteem) and pacce (solidarity) reshaped his concept of masculinity. Initially, Arung Palakka's masculinity was tied to status and lineage, which was shattered when the Kingdom of Gowa-Tallo enslaved him and his people. This experience did not destroy him; instead, it transformed his personal siri' into a collective siri', motivating him to fight for the honor of his people. This shift formed a pragmatic and strategic masculinity, distinct from the to warani ideal that relied solely on physical bravery. His crucial, albeit controversial, decision to ally with the VOC (Dutch East India Company) is proof of this new masculinity, an action that prioritized collective liberation over traditional idealism. The victory in the Makassar War not only restored sovereignty but also the dignity of the Bugis people, making Arung Palakka a symbol of Leadership born from suffering and strengthened by solidarity. Overall, Arung Palakka is not merely a military hero but a representation of evolving masculinity. He demonstrated that true strength lies not in domination or arrogance, but in the ability to empathize, serve the people, and transform trauma into power for the common good.